Characteristics of oral microbiota in plateau and plain youth‐positive correlations between blood lipid level, metabolism and specific microflora in the plateau group - Zhao, LiBo; Wang, Huanhuan; Gao, Yinghui; Hao, Benchuan; Li, Xueyan; Wen, Ruoqing; Chen, Kaibing; Fan, Li; Liu, Lin (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: To analyze the characteristics of oral microbiota in plateau and plain youth and the possible function of the microbiome. Materials and methods: A total of 120 healthy young males (80 on the plateau, 40 on the plain) completed this cross-sectional study. Oral microflora samples were collected from all participants. The bacterial 16S rDNA was amplified using PCR and sequenced using Illumina MiSeq high-throughput sequencing. The data were analyzed to determine the microbial distribution and community structure of the oral microflora from the two groups. Metastats was used to test differences in relative species abundance between the groups. The correlation between the abundance of specific bacteria and blood indicators was also analyzed. Results: As demonstrated by alpha and beta diversity, the plateau group had lower microbial richness and a less even distribution of oral microbiota than the plain group. All predominant phyla and genera were qualitatively similar between the two groups, but their relative abundances differed. The relative abundance of bacteria in the phylum Firmicutes was significantly higher in the plateau group than in the plain group. At the genus level, Streptococcus spp. and Gemella spp. were also more abundant in the plateau group. The functional prediction indicated vigorous microbial metabolism in the oral bacterial community. We also found that the relative abundance of Streptococcus spp., the dominant genus, was positively correlated with triglyceride levels in the plateau group. Conclusions: With increasing altitude, the diversity of oral microbiota and the relative proportion of predominant bacteria were altered. The distribution and related function of Streptococcus spp. were prominent in plateau samples. This comprehensive study of the relationship between oral microecology and elevation provides a point of reference for studying the human body's adaptability or inadaptability to high altitude.